Reconstructing the Principle of Propriety: Towards Legal Certainty in Indonesia Contracts Law - Ariyanto Ariyanto (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
This study examines the regulation and implementation of the propriety principle in Indonesian contract law, addressing the continuing uncertainty surrounding its criteria and judicial application. Although the principle is recognized in legislation and court practice, the absence of clear standards has led to inconsistent interpretations, potentially affecting legal certainty and fairness in contractual relationships. The research aims to evaluate whether the existing criteria for the propriety principle require further clarification and reinforcement within the Indonesian legal framework. Employing a normative legal research method, the study analyses statutory regulations, court decisions with permanent legal force, and relevant legal theories proposed by Van Dunne, Arthur L. Corbin, Robin Kar, and Bertram Lomfeld. The findings indicate that the propriety principle should be interpreted in close relation to the doctrine of good faith and the concepts of contract as deliberation and contract as empowerment. Moreover, the meeting of minds between contracting parties is identified as the fundamental mechanism through which propriety is realized in contractual agreements. This study contributes to the development of Indonesian contract law by offering a more coherent theoretical framework and practical guidance for judges, legal practitioners, and policymakers in interpreting and applying the propriety principle consistently